Microbial catabolic activity: methods, pertinence, and potential interest for improving microbial inoculant efficiency - Ndour, Papa Mamadou Sitor; Bargaz, Adnane; Rchiad, Zineb; Pawlett, Mark; Clark, Ian M.; Mauchline, Tim H.; Harris, Jim A.; Lyamlouli, Karim (Springer, 2023)
Microbial catabolic activity (MCA) defined as the degrading activity of microorganisms toward various organic compounds for their growth and energy is commonly used to assess soil microbial function potential. For its measure, several methods are available including multi-substrate-induced respiration (MSIR) measurement which allow to estimate functional diversity using selected carbon substrates targeting specific biochemical pathways. In this review, the techniques used to measure soil MCA are described and compared with respect to their accuracy and practical use. Particularly the efficiency of MSIR-based approaches as soil microbial function indicators was discussed by (i) showing their sensitivity to different agricultural practices including tillage, amendments, and cropping systems and (ii) by investigating their relationship with soil enzyme activities and some soil chemical properties (pH, soil organic carbon, cation exchange capacity). We highlighted the potential of these MSIR-based MCA measurements to improve microbial inoculant composition and to determine their potential effects on soil microbial functions. Finally, we have proposed ideas for improving MCA measurement notably through the use of molecular tools and stable isotope probing which can be combined with classic MSIR methods.
Keywords: Microbial catabolic activity; CLPP; Soil quality indicators; Soil function; Microbial inoculant efficiency